Pengaruh Work Family Conflict, Komitmen Organisasi Terhadap Turnover Intention Dengan Kepuasan Kerja Sebagai Variabel Intervening - Lestari, Diana; Prahiawan, Wawan (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2018)
Work family conflict is one of the problem that must be faced by employees. This conflict occurs because the working hours and workload which is owned by an employee is too dense, so that all the attention and mind too on one role only.which in turn leads to the employee turnover intention.This study aims to explore the effect of work-family conflict and Organizational commitment , job satisfaction and turnover intention PT. Tomo & Son. The sample in this study were 91 employees of the PT.Tomo & Son. The data collection technique used was questionnaire. The data analysis technique used was Structural Equation Model (SEM) with SmartPLS (Partial Least Squares).The results showed that: (1) work-family conflict have negative effects significantly to job satisfaction; (2) Organizational commitment have positive effects significantly to job satisfaction; 3) work-family conflict have positive effects significantly to turnover intention; 4) Organizational commitment no have negative effects significantly to turnover intention (5) job satisfaction have negative effects significantly to turnover intention